2017
DOI: 10.3892/mmr.2017.7641
|View full text |Cite
|
Sign up to set email alerts
|

PDGF signaling pathway in hepatic fibrosis pathogenesis and therapeutics

Abstract: The platelet-derived growth factor (PDFG) signaling pathway exerts persistent activation in response to a variety of stimuli and facilitates the progression of hepatic fibrosis. Since this pathway modulates a broad spectrum of cellular processes, including cell growth, differentiation, inflammation and carcinogenesis, it has emerged as a therapeutic target for hepatic fibrosis and liver-associated disorders. The present review exhibits the current knowledge of the role of the PDGF signaling pathway and its pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
124
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(138 citation statements)
references
References 119 publications
4
124
0
1
Order By: Relevance
“…ERKs play a central role in cell survival and mitogenic signaling, while the JNK and p38 MAP kinases induce various stress responses, including apoptosis, inflammation, and differentiation [29]. Various studies have reported that ERK acts downstream of the PDGF pathway and regulates cell proliferation [30]. Both fresh-PRP and FD-PRP activated PDGFR and its downstream target ERK in osteoblasts, indicating that PDGF concentration in PRP is sufficient to induce the proliferation of osteoblasts via the PDGFR-mediated ERK signaling pathway (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…ERKs play a central role in cell survival and mitogenic signaling, while the JNK and p38 MAP kinases induce various stress responses, including apoptosis, inflammation, and differentiation [29]. Various studies have reported that ERK acts downstream of the PDGF pathway and regulates cell proliferation [30]. Both fresh-PRP and FD-PRP activated PDGFR and its downstream target ERK in osteoblasts, indicating that PDGF concentration in PRP is sufficient to induce the proliferation of osteoblasts via the PDGFR-mediated ERK signaling pathway (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, it is reasonable to propose that Reb A, similar to stevioside, may protect the liver by exerting the immunomodulatory and antifibrogenic effects, downregulating the NF‐κB pathway and modulating the MAPK pathway. Another pathway, the PDGF pathway, modulates a broad spectrum of cellular responses, such as cell growth, differentiation, inflammation and carcinogenesis, actively participating in HSC activation during the early stage of liver injury and exacerbating the production of ECM (Ying et al, ). Therefore, modulation of the PDGFR by Reb A could explain, at least in part, the beneficial effects of Reb A observed in cocultured cells and in rat‐induced chronic liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced levels of the pro‐inflammatory MIP‐1a also indicate that Th1 inflammation is affected. PDGF is a growth factor highly involved in the development of liver fibrosis and is associated with chronic inflammation . Chemokines (as RANTES or chemokine ligand 5) are relevant in allergy because of their role in regulating leukocyte recruitment, but also for cellular activation, inflammatory mediator release, promotion of Th2 inflammatory responses, and regulation of IgE .…”
Section: Discussionmentioning
confidence: 99%
“…PDGF is a growth factor highly involved in the development of liver fibrosis and is associated with chronic inflammation. 30,31 Chemokines (as RANTES or chemokine ligand 5) are relevant in allergy because of their role in regulating leukocyte recruitment, but also for cellular activation, inflammatory mediator release, promotion of Th2 inflammatory responses, and regulation of IgE. 32 RANTES has been linked to recruitment of Th2 cells, 33 and TNFα is thought to play a major role in the pathogenesis of allergy and inflammatory diseases as it is produced at an early stage of allergen sensitization and continues to promote the inflammation cascade throughout the allergy development.…”
Section: Discussionmentioning
confidence: 99%